PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV MELALUI MODEL PEMBELAJARAN PBL (PROBLEM BASED LEARNING) BERBASIS TGT (TEAM GAMES TURNAMENT) - Juli Sugianingsih; Winda Luthfiyaningrum; Dewi Tryanasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problems that occurred in this research were the low learning outcomes of Mathematics content, caused by the use of limited learning media, learning was less interesting and less enjoyable because the learning models and methods were less varied, students were still hesitant in expressing their opinions on the material they were studying. This research aims to improve mathematics learning outcomes in fourth grade elementary school students through the PBL (Problem Based Learning) learning model based on TGT (Team Games Tournament). This classroom action research was carried out in 2 cycles with each cycle having four stages, namely: planning, implementation , observation and reflection. The subjects of this research were 28 class IV students at SDN 02 Madiun Lor. The results of this research show that Mathematics for class IV students through the PBL (Problem Based Learning) learning model based on TGT (Team Games Tournament) can improve student learning outcomes which are characterized by increased completeness, namely in cycle 1 with an average score of 78.88, while in cycle with an average score of 86.60 and was declared successful.